The Authority of a Notary in Drafting a Deed of Sale and Purchase of Uncertified Land - Muhammad Daffa Verandy; Elvira Fitriyani Pakpahan; Rodiatun Adawiyah; Muhammad Ali Adnan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Land, due to its high economic and social value, often becomes a source of legal disputes, particularly in transactions involving unregistered land. In practice, the public frequently engages a Notary to draft a deed as evidence of a legal act, even though the actual authority to transfer land rights lies with the Land Deed Official (PPAT). This study aims to examine the Notary’s authority in drafting deeds of sale and purchase of unregistered land and analyze the legal consequences of such deeds. Using a normative legal research method with statutory, conceptual, and case approaches, the study finds that a Notary’s authority in these transactions is limited: the Notary may prepare a deed as evidence of an agreement or obligation but cannot directly effect the transfer of land rights. The Notary’s responsibility primarily concerns the formal correctness of the deed, yet civil, administrative, ethical, or even criminal liability may arise if negligence or professional misconduct occurs. The study emphasizes the importance of prudence, thorough verification, and legal counseling by Notaries to protect parties’ interests and uphold the integrity of the Notarial profession in unregistered land transactions.